ANALISIS AUTOKORELASI SPASIAL KONSUMSI ALKOHOL PADA 514 KABUPATEN/KOTA DI INDONESIA - Muhammad Syukri (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2026)
Alcohol consumption poses a public health challenge because it can lead to various health problems. Although the prevalence of alcohol consumption in Indonesia is relatively lower compared to other countries, data from the 2023 Indonesian Health Survey (Survei Kesehatan Indonesia/SKI) indicate considerable regional variation in consumption rates. This study aims to analyze the spatial distribution patterns of alcohol consumption prevalence across 514 districts/cities in Indonesia in 2023. The study employed a quantitative approach with an ecological study design using secondary data obtained from the 2023 Indonesian Health Survey (SKI). The unit of analysis included all 514 districts/cities. Univariate Global and Local Moran’s Index using Geoda was employed to identity the hotspots and cold spots of alcohol consumption at city and district level. The results revealed significant positive spatial autocorrelation of alcohol consumption in most of Indonesia regions, particularly in Sumatra (p value=0.001, Moran’s Index=0.513), Java (p value=0.005, Moran’s Index=0.205), Kalimantan (p value=0.001, Moran’s Index=0.452), Bali and Nusa Tenggara (p value=0.001, Moran’s Index=0.795), and Sulawesi (p value=0.001, Moran’s Index=0.493). Hotspots of alcohol consumption prevalence were primarily identified in East Nusa Tenggara, North Sulawesi, and several districts in Kalimantan and Sumatra. In conclusion, alcohol consumption in Indonesia forms distinct regional clusters, highlighting the need for more effective area-based interventions.